The Challenges Facing Participants Integration of ICT Skills and Equipment into the Classroom in Saudi Secondary Schools. - Alkahtani, Aishah Abdulaziz Abdulaziz (Social Science Learning Education Journal, 2016)
A study was conducted of the effectiveness of the information and communications technology component (ICT) of the King Abdullah project. This study presents two significant shortcomings: A lack of training and a lack of working equipment. The results also show a lack of understanding among both students and teachers of how the equipment functions; a lack of mastery of ICT teaching techniquesâand a lack of teacher training. The findings suggest expanding decision-making authority to key players from all levelswill result in the program functioning more effectively.